2002
DOI: 10.2174/0929867023369745
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peripheral Benzodiazepine Receptors (PBRs) in CNS Pathophysiology

Abstract: The peripheral benzodiazepine receptors (PBRs) have been identified to bind selectively benzodiazepine ligands and an isoquinoline carboxamide derivative PK 11195 with high affinity. PBRs are present in the central nervous system (CNS), peripheral tissues, and most organs in the human body. PBRs are different from the central benzodiazepine receptors (CBRs) related to the nerve cell membrane GABA(A) receptor and are thought to play several physiological and pathophysiological functions in the CNS and immune sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 27 publications
1
47
0
1
Order By: Relevance
“…In the CNS, PBRs are mainly located in glial cells, particularly in microglia and astrocytes, with highest densities in the olfactory bulb, choroid plexus, and the ependymal lining of the ventricles [17,30]. In the CNS, PBRs participate in multiple physiological functions including neurosteroid synthesis, nutritional support of neurons, and modulation of CNS immune reactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the CNS, PBRs are mainly located in glial cells, particularly in microglia and astrocytes, with highest densities in the olfactory bulb, choroid plexus, and the ependymal lining of the ventricles [17,30]. In the CNS, PBRs participate in multiple physiological functions including neurosteroid synthesis, nutritional support of neurons, and modulation of CNS immune reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of microglia also may indicate that they are performing some protective functions such as releasing neurotrophic factors and protecting cells from damage [32,34,35]. Various studies have demonstrated that PBRs are involved in numerous nervous system disorders such as multiple sclerosis, cerebral ischemia and stroke, epilepsy, brain injury, neurotoxic brain damage, and neurodegenerative diseases [17,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the CNS, PBRs are mainly located in glial cells, particularly in microglia and astrocytes, with the highest densities in the olfactory bulb, choroid plexus, and ependymal lining of the ventricles [14,11]. In the CNS, PBRs participate in multiple physiological functions including neurosteroid synthesis, nutritional support of neurons and modulation of CNS immune reactions.…”
Section: Discussionmentioning
confidence: 99%